Model Pembelajaran Religious Culture Sebagai Basis Pengembangan Kurikulum Pendidikan Islam - Rachman, Lutfi (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2022)
Humans are social beings who need each other to form social groups in the environment of their daily lives. Religion is a value system that is adhered to by society that can shape the style and dynamics of social life, because religion is a source of inspiration, driving force and also acts as a controller for the continuity and peace of human life in a social group or society. In carrying out its duties and functions as a social being, religious values ​​are very much needed. The implementation of character education needs to be developed in a habituation or acculturation approach through religious culture which is essentially closely related to character education, namely trying to produce students who are moral or have good behavior. Then the focus in this problem is education. Because education is one way out to foster the character of the younger generation in a directed, programmed, and optimal way so that they can form a young generation who is intellectually intelligent and has good moral qualities.